Spoken word in the UK - English, Lucy; McGowan, Jack 1989- (Routledge, Taylor & Francis Group, 2021)
"Spoken Word in the UK is a comprehensive and in-depth introduction to spoken word performance in the UK - its origins and development, its performers and audiences, and the vast array of different styles and characteristics that make it unique. Drawing together a wide range of authors including scholars, critics, and practitioners, each chapter gives a new perspective on performance poetics. The book's six sections cover the essential elements of understanding the form and discuss how this key aspect of contemporary performance can be analysed stylistically, how its development fits into the context of performance in the UK, the ways in which its performers reach and engage with their audiences, and its place in the education system. Each chapter is a case study of one key aspect, example, or context of spoken word performance, combining to make the most wide-ranging account of this form of performance currently available. This is a crucial and ground-breaking companion for those studying or teaching spoken word performance, as well as scholars and researchers across the fields of theatre and performance studies, literary studies, and cultural studies"--
Keywords: Lyrik; Aufführung; Englisch; Spoken word poetry, English / History and criticism; Criticism, interpretation, etc; Aufsatzsammlung